Peningkatan Daya Saing UMKM melalui Edukasi Halal dan Pendampingan Pemasaran Berbasis Teknologi: Improving the Competitiveness of MSMEs through Halal Education and Technology-Based Marketing Assistance - Raehana, Syarifa; Ummu Kalsum; Elena Mariantika; Fauziah Ahmad (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program (PKM) aims to improve the ability of Micro, Small, and Medium Enterprise (MSME)s to understand and comply with halal-thayyib standards and prepare halal certification documents, and to improve MSME skills in utilizing digital marketing to expand promotions and increase product sales. The methods used in implementing this activity are 4 (four), namely; Workshop, Simulation, Mentoring and Evaluation. This activity involved 16 (sixteen) MSME actors engaged in the culinary sector. The results of this Community Service Activity were able to improve the understanding of MSME partners about halal literacy, including the concept of halal-thayyib, the certification process, and the required documentation. Of the 16 business actors, 3 (three) of them have successfully obtained halal certification, 6 (six) are in the process of applying, and the rest are completing the requirements, indicating an increase in partner readiness in meeting halal regulatory standards. Regarding marketing system assistance, training and mentoring activities strengthen partners' abilities in utilizing social media as a promotional tool. While there are still limitations in the use of certain platforms, ongoing support through the creation of new accounts and simple promotional practices has had a positive impact, increasing the visibility and sales of MSME products. Overall, these PKM activities have significantly contributed to increasing the capacity of partners in halal legality and digital marketing.